Influência das alvenarias de preenchimento na determinação do período fundamental de edifícios de concreto armado - Silva, Emerson Rodrigues da (2021)
In structures of building, an adequate estimate of its dynamic properties may be required. In particular, there is the fundamental period, necessary, for example, in the use of the method of equivalent horizontal forces for seismic analyses or in the consideration of the dynamic effects of wind in slender structures. The presence of filling masonry is among the various parameters that affect the fundamental period of a structure. In the literature and normative codes there are several approximate expressions for determining the Fundamental Period of concrete frames, however, the vast majority considers only the influence of the structure’s total height, disregarding several other factors such as: the presence of filling masonry; the elasticity module; and the openings presented in the masonry. In addition, these approximate expressions present divergent results. In this paper, several numerical simulations were carried out to determine the fundamental period in reinforced concrete frames filled with masonry for different elasticity modules and percentages of openings. The results of the modal analysis (via the ANSYS program) allowed the qualitative and quantitative comparison of the fundamental periods of buildings between the following situations: i) without considering infilled masonry; ii) with the consideration of the stiffness of the infilling masonry (without openings and with openings). The modal analysis also allowed comparison with the main analytical expressions found in the literature (including standards) to approximate the fundamental periods. The results confirm that masonry promotes the reduction of the fundamental period, however, it is less influential for wall openings greater than 60%. In addition, relevant differences were observed between the fundamental periods estimated with the analytical expressions and those obtained with the modal analyses.